2003
DOI: 10.3121/cmr.1.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Thymoma and Multiple Malignancies: A Case of Five Synchronous Neoplasms and Literature Review

Abstract: The presence of five discrete synchronous or metachronous primary neoplasms in a single patient is an extremely rare event. This is a report of a patient with a malignant (invasive) thymoma and four other independent primary neoplasms including: gliosarcoma, papillary thyroid cancer, meningioma and metastatic adenocarcinoma of the colon, found synchronously at autopsy. Thymoma patients appear to have an inherent predisposition towards developing additional neoplasms. Other than the thymoma, the presented patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 44 publications
1
24
1
Order By: Relevance
“…Few other case reports describe the asociation of thyroid carcinomas with thymomas [16,22]. An additional feature in our case was thymoma positivity for transcription factor TTF1 (Thyroid Transcription Factor 1, otherwise known as NKX2-1, NK2 Homeobox 1).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Few other case reports describe the asociation of thyroid carcinomas with thymomas [16,22]. An additional feature in our case was thymoma positivity for transcription factor TTF1 (Thyroid Transcription Factor 1, otherwise known as NKX2-1, NK2 Homeobox 1).…”
Section: Discussionmentioning
confidence: 63%
“…Interestingly, five cases of thyroid tumors were registered. The fact that these tumors were often diagnosed prior to or concomitant with thymomas suggested that a predisposition to cancer may underlay the association rather than thymoma treatment [16].…”
Section: Discussionmentioning
confidence: 99%
“…[3840] Several authors have previously reported synchronous glioma and meningioma. Literature review shows that glioblastoma is the most frequent glioma subtype associated.…”
Section: Discussionmentioning
confidence: 99%
“…By gross examination, thymoma is a lobulated and firm tumor, has tan-pink to gray color and contains cystic spaces, calcification or hemorrhage. In addition, it is encapsulated and invasive and frequently adheres to the surrounding structures 9 . Our patient had a gray mass that infiltrated into the adjacent connective tissue.…”
Section: Discussionmentioning
confidence: 99%